Genetics of Field Resistance of Rice to Brown Planthopper - Velusamy, R.; Heinrichs, E.A.; Khush, G.S. (Wiley, 1987)
The brown planthopper [Nilaparvata lugens (Stal)] is one of the most serious insect pests of rice (Oryza sativa L.) in South and Southeast Asia. Because cultivars with vertical resistance to brown planthopper have “broken down” due to brown planthopper biotype selection, field resistant cultivars with horizontal resistance are being evaluated. The inheritance of field resistance to brown planthopper in two traditional rice cultivars, ‘Utri Rajapan’ and ‘Triveni’, was investigated. Twenty‐day old seedlings were infested with second and third‐instar brown planthopper nymphs. Reactions of F1, F2, and F3 populations from the crosses of resistant cultivars with the susceptible parent ‘TN1’ revealed that two independently segregating recessive genes govern resistance in both cultivars. Allelism tests revealed that the two cultivars have the same genes for resistance.